EFEKTIVITAS TRICHODERMA DAN PUPUK KANDANG TERHADAP PERTUMBUHAN TINGGI DAN DIAMETER SEMAI ACACIA MANGIUM PADA TANAH ULTISOL - Hardianus, .; Suryantini, Rosa; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2017)
This research aimed to obtain a dose of Trichoderma sp. and manure that effective on the growth of Acacia seedlings in Ultisol soil. The research design was a Factorial Complete Random Design that is consisting of 2 (two) factors which are dose of Trichoderma sp. and dose of cow manure. Dosage of Trichoderma sp. consisting of: 0 gr/polybag (T0), 5 gr/polybag (T1), 10 gr/polybag (T2), and 15 gr/polybag (T3). Dosage of cow manure consisting of: 0 gr/polybag (K0), 50 gr/polybag (K1), 100 gr/polybag (K2), and 150 gr/polybag (K3). Each treatment was repeated 3 (three) times so that the total amount of treatment was 48 seedlings. The parameters observed were the height and diameter of the seedlings carried out for 2 (two) months at the Silviculture Laboratory of Forestry Faculty, Tanjungpura University.Â  The result showed the dose of Trichoderma sp., manure and its interaction had no significant effect on the growth of seedlings height. Dose of Trichoderma sp. was very significant effect on the growth of seedlings diameter, while manure and its interaction have no real effect. The best dose for seedlings diameter growth is T3K2 treatment (dosage 45 gram Trichoderma sp. and 100-gram cow manure). Keywords: Acacia mangium, Manure, Trichoderma sp.